THE INFLUENCE OF PRESENCE OF FEMALE IN BOARD OF DIRECTORS AND AUDIT COMMITTEE TOWARDS FINANCIAL PERFORMANCE: EVIDENCE FROM INDONESIAN PUBLIC COMPANIES - Putri, Devana Alyaa Purnomo; Kurniawan, Budi Kurniawan,; Pulungan, Andrey Hasiholan (Jurnal Akuntansi Bisnis, 2024)
Background:  Diversity on corporate boards and strong audit committees are essential for good corporate governance, and promoting gender diversity, particularly increasing the number of women on boards, has been proven to enhance overall business performance.Objective: This study aims to investigate whether the presence of women in the board of directors and audit committee affects the financial performance of Indonesian public companies listed on the Indonesia Stock Exchange (IDX). The study uses a purposive sampling method to select 670 companies from financial statements listed on IDX from 2019 to 2021, excluding the financial industry.Research Method: The study employed multiple linear regression analysis with a fixed effect model and an ordinary least square (OLS) model to assess ROA and PER. Recognizing the presence of heteroskedasticity and autocorrelation issues, the regression was adjusted using Robust Standard Error for standardization.Research Result: This study shows that having women on the board of directors positively influences Return on Assets (ROA) and negatively influences Price-to-Earnings Ratio (PER). Although the study did not find a significant influence of women on the audit committee, it suggests that the presence of women on boards of directors can potentially improve companies' financial performance.Research Originality/Novelty: The authors emphasize that their study fills a gap in the literature by examining the impact of female presence in board of directors and audit committees on financial performance in Indonesian public companies.